Mini Dental Implant-Retained Removable Partial Dentures: Treatment Effect Size and 6-Months Follow-up - Visar Disha; Asja Čelebić; Ksenija Rener-Sitar; Ines Kovačić; Irina Filipović Zore; Sanja Peršić (University of Zagreb. School of Dental Medicine, 2018)
Objective: The aim was to compare esthetic outcomes, masticatory performance and a comfort of removable partial denture (RPD) wearing after receiving: clasp-retained RPD (C-RPD) or mini dental implant- retained RPD (MDI-RPD) in the mandible. Materials and Methods: A sample of 88 patients (Kennedy Class I) with all posterior teeth missing and a linear support for a RPD participated. A total of 52 patients (36 females, 16 males; 56 to 84 years old) participated in the C-RPD group and 36 patients (26 females, 10 males; 43 to 81 years old) in the MDI-RPD group. All MDIs were placed adjacent to the last remaining mandibular anterior tooth or one tooth length posteriorly. The new RPDs had Co- Cr frameworks with lingual plate major connectors; the MDI-RPDs were retained by O-ball matrices and the C-RPDs with clasps. Patients answered questions at pre-treatment and post-treatment stages and after 6-months follow-up: how satisfied they had been with esthetic appearance, how confident they were while chewing hard food, how satisfied they were with food comminution and they also evaluated a comfort of RPD wearing. The 0-10 visual-analogue scale was used. Statistics included descriptive methods, t-tests and the standardized effect-size calculation. Results: The MDI-RPD wearers were more satisfied with their post-treatment esthetics, food comminution, a comfort with RPDs and had better confidence while chewing than the C-RPD wearers. The MDI-RPD wearers reported larger positive effect of the treatment. The results were consistent throughout the first 6-months period. Conclusion: The MDI-RPD patients showed superior outcomes than the C-RPD patients after the treatment and over the 6-month period.